2020
DOI: 10.1001/jamaoto.2019.2877
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Barriers to Timely Access to Pediatric Hearing Aids

Abstract: IMPORTANCE Despite various barriers identified to early pediatric access to cochlear implantation, barriers to timely access to pediatric hearing aids are not well characterized.OBJECTIVE To identify socioeconomic, demographic, and clinical factors that may be associated with pediatric access to hearing aids. DESIGN, SETTING, AND PARTICIPANTSThis retrospective cohort study included 90 patients aged 1 to 15 years who were referred for auditory brainstem response (ABR) testing and evaluation for hearing aids at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 22 publications
1
34
1
Order By: Relevance
“…Black patients were more likely both to reschedule tympanostomy tube placement and experience cancelation of tympanostomy tube placement. This is consistent with other studies, including hearing aid access and ABR testing, 14 as well as cochlear implantation. 22 Reasons for delays in care between different races/ethnicities may include difficulty accepting the diagnosis, 23 language barriers or cultural beliefs, 24 and socioeconomic factors that impact ability to attend scheduled surgical appointments.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Black patients were more likely both to reschedule tympanostomy tube placement and experience cancelation of tympanostomy tube placement. This is consistent with other studies, including hearing aid access and ABR testing, 14 as well as cochlear implantation. 22 Reasons for delays in care between different races/ethnicities may include difficulty accepting the diagnosis, 23 language barriers or cultural beliefs, 24 and socioeconomic factors that impact ability to attend scheduled surgical appointments.…”
Section: Discussionsupporting
confidence: 93%
“…The impact of insurance type on delay to surgical care has been shown for various otolaryngologic surgeries, including upper airway stimulation, 13 adenotonsillectomy, 6 auditory brainstem response testing, 14 cochlear implantation, 15 and head and neck cancer treatment, 16 with publicly insured patients demonstrating higher rates of delay. Patients in our study who were insured by Medicaid at the time of their clinic visits had 40% higher odds of rescheduling the surgery than privately insured patients.…”
Section: Insurance-related Factorsmentioning
confidence: 99%
“…For pediatric hearing aid use, we incorporated time to uptake data to inform yearly probabilities of acquiring hearing aids (age 1 year: mean=15.8 months, SD=16.8 months; ages 2–5 years: 31.68 months, SD=18.32 months). 46 , 47 We assumed a linear decline in hearing aid acquisition from age 5 years to adulthood. Combined with a discontinuation rate of 3%/year, we projected the yearly proportion of children with aidable hearing loss (defined as PTA≥25 dB in the better ear) using hearing aids.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to hearing healthcare specifically, previous studies have demonstrated significantly higher rates of hearing aid use among White older adults as compared to minority groups (28.6–35.4% of White older adults vs. 10–17.1% of minorities) ( 30 , 32 , 34 ). In pediatric patients, Zhang et al ( 35 ) found a relationship between race/ethnicity and the time delay between a failed newborn hearing screening and initial auditory brainstem response (ABR) testing. The mean interval for White patients was 6.3 months [standard deviation (SD): 5.6 months] compared to 12.3 months (SD: 11.8 months) for racial/ethnic minority patients.…”
Section: Barriers To Hearing Healthcarementioning
confidence: 99%
“…Thus, it begs the question-what most contributes to the lack of care, and how can this be improved? While reasons vary from community-to-community and from individualto-individual, common factors include cost of services (18)(19)(20), a shortage of clinical providers/specialized services (21)(22)(23)(24)(25)(26), inconvenience of travel (24,27), communication barriers (28,29), and racial/ethnic disparities (30)(31)(32)(33)(34)(35). The COVID-19 pandemic, with its associated lockdowns and social distancing requirements, led to mass disruption in the delivery of healthcare services worldwide.…”
Section: Introductionmentioning
confidence: 99%